Stripping of Vegetable Oils by Direct Mixing with Adsorbent Materials - Berton-Carabin, Claire C.; Ribourg-Birault, Lucie; Benatti Gallo, Thais Cristina [UNESP] (Springer Nature, 2024)
It is often useful to conduct experiments with triacylglycerol oils, such as vegetable oils, that have been stripped from surface-active impurities and/or endogenous antioxidants. This chapter describes a rapid, simple, and solvent-free procedure to achieve such purification by the direct mixing of oil with an adsorbent powdered material (magnesium silicate or aluminum oxide), followed by gravitational separation. In particular, we give a step-by-step description of the method, as well as practical tips, and provide experimental data regarding the properties of a comprehensive set of oils obtained via this procedure.